Fair play : diretrizes para o design de audiogames para usuários com deficiência para usuários com deficiência visual - Borges, Olimar Teixeira (2018)
In the context of Informatics in Education and Assistive Technologies, research we can be observe the lack of the application of guidelines for the development of accessible games. In this way, in general, each developer group is immersed in a differentiated set of recommendations, without knowing how to identify priorities, because they often lack experience with people with disabilities. Thus, with the need to find specific recommendations for the development of games accessible to visually impaired users, we conducted a survey to verify the process of building these games. In the context of this study, the term “audiogame” is being used to define guidelines based on sound interface. Thus, in the first instance, the study in question, through one of the techniques of literature review, called Snowballing, identified sets of guidelines aimed at the development of games accessible in general. This study resulted in some sets of guidelines, which were developed with the focus on the creation of a audiogames development guide. Based on data collection through online questionnaires and a Focal Group, the guidelines were evaluated alongside visually impaired users and with developers of audiogames, aiming at consolidating the literature with what is in practice. As a result, a guide with 33 guidelines, called Fair Play, for the audiogames design has been made available and also published in a web environment, so that a greater number of developers interested in this type of development, can have access to it.